Harun Farocki : working on the sightlines - Farocki, Harun; Elsässer, T. (Thomas) (Amsterdam : Amsterdam University Press, 2004)
The first English-language book on Germany's 'best-known important filmmaker'.
Harun Farocki : filmmaker, artist, media theorist / Thomas Elsaesser -- Painting pavements / Volker Siebel -- Images and thoughts, people and things, materials and methods / Jörg Becker -- Incisive divides and revolving images : on the installation Schnittstelle / Christa Blümlinger -- Passage along the shadow-line : feeling one's way towards the Filmkritik-style / Olaf Möller -- The green of the grass : Harun Farocki in Filmkritik / edited by Rainer Knepperges -- Staking one's life : images of Holger Meins / Harun Farocki -- Working at the margins : film as a form of intelligence / Thomas Elsaesser -- Dog from the freeway / Harun Farocki -- Political filmmaking after Brecht : Farocki, for example / Thomas Elsaesser -- The road not taken : films by Harun Farocki / Jonathan Rosenbaum -- Slowly forming a thought while working on images / Christa Blümlinger -- Making the world superfluous : an interview with Harun Farocki / Thomas Elsaesser -- Reality would have to begin / Harun Farocki -- Light weapons / Tom Keenan -- The political im/perceptible : Images of the world -- / Nora Alter -- Workers leaving the factory / Harun Farocki -- On media and democratic politics : Videograms of a revolution / Benjamin Young -- Towards an archive for visual concepts / Wolfgang Ernst and Harun Farocki -- Controlling observation / Harun Farocki -- Nine minutes in the yard : a conversation with Harun Farocki / Rembert Hüser -- Harun Farocki : critical strategies / Christa Blümlinger.
Includes indexes.
Includes Farocki: a filmography.
eBooks on EBSCOhost
Keywords: Farocki, Harun -- Criticism and interpretation; Farocki, Harun; Motion picture producers and directors -- Germany -- Biography; The arts; Film, TV and radio; PERFORMING ARTS -- Film & Video -- Direction & Production; BIOGRAPHY & AUTOBIOGRAPHY -- Entertainment & Performing Arts; Motion picture producers and directors; Germany; Humaniora -- Film; Biographies; Criticism, interpretation, etc; Biographies; Biographies